Contingent Liabilities : Issues and Practice - Cebotari, Aliona (Washington, D.C. : International Monetary Fund, 2008)
Contingent liabilities have gained prominence in the analysis of public finance. Indeed, history is full of episodes in which the financial position of the public sector is substantially altered-or its true nature uncovered-as a result of government bailouts of financial or nonfinancial entities, in both the private and the public sector. The paper discusses theoretical and practical issues raised by contingent liabilities, including the rationale for taking them on, how to safeguard against the fiscal risks associated with them, how to account and budget for them, and how to disclose them. Country experiences are used to illustrate ways these issues are addressed in practice and challenges faced. The paper also points to good practices related to the mitigation, management and disclosure of risks from contingent liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet